The Charter and Code of the Ordinances of Yazoo City 174, ch. 20, § 297 (1908). - (:unkn) unknown (General Publisher, 1906)
It shall not be lawful for any person to sell, give, or lend to any minor or person intoxicated, knowing him to be a minor or in a state of intoxication, any deadly weapon, or other weapon the carrying of which concealed is prohibited, or pistol cartridge; and, on conviction thereof, he shall be punished by a fine of not less than twenty-five dollars nor more than two hundred dollars, or imprisoned not exceeding ninety days, or both.
--
Keywords: TRANSFER - MINORS; TRANSFER - INCOMPETENTS